Порівняння фармакодинаміки низькомолекулярних гепаринів у профілактиці венозного тромбоемболізму під час операцій з приводу раку щитоподібної залози - Черній, В. І.; Єгоров, А. А.; Смирнова, Н. Н.; Єгоров, А. Н.; Босько, І. Л. (Clinical Endocrinology and Endocrine Surgery, 2011)
In given article influence of Zibor (Bemiparin sodium) on anti-Xa activity of plasma as well as on standard indices of coagulogram at start therapy in 12 hours prior to operation in comparison with others low molecular weight heparins for preventive maintenance of venous thromboembolism at surgical treatment of a cancer of a thyroid gland is studied. Increase in anti-Xa activity in 12 hours after administration of Zibor in comparison with Endoxaparine as well as lower influence on thrombin, prothrombin and activated partial thromboplastin times variability are proved in comparison with Fraxiparine and Fragmin.